2019
DOI: 10.1186/s12885-019-5462-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of cancer-associated fibroblast markers at the invasive front and its association with tumor-stroma ratio in colorectal cancer

Abstract: Background The tumor microenvironment has a critical role in regulating cancer cell behavior. Tumors with high stromal content are associated with poor patient outcome. The tumor-stroma ratio (TSR) identifies colorectal cancers (CRC) with poor patient prognosis based on hematoxylin & eosin stained sections. The desmoplastic reaction consists to a great extent of cancer-associated fibroblasts (CAFs) of which different subtypes are known. The aim of this study is to investigate and quantify CAFs pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 24 publications
4
108
0
2
Order By: Relevance
“…Our studies are the first to have measured CXCR4 in matched isolated malignant colonocytes and tumor-associated stroma by Western blotting. For the first time, we also observed that CXCR4 mRNA expression levels were higher in tumor-associated stromal cells compared to control stromal cells, suggesting that CXCR4 may play a critical role in regulating the tumor microenvironment as observed for other genes that are highly expressed in CRC-associated stromal cells [60,61]. The expression patterns of CXCR4 in our study were consistent with prior reports that analyzed CXCR4 expression in CRC.…”
Section: Discussionsupporting
confidence: 91%
“…Our studies are the first to have measured CXCR4 in matched isolated malignant colonocytes and tumor-associated stroma by Western blotting. For the first time, we also observed that CXCR4 mRNA expression levels were higher in tumor-associated stromal cells compared to control stromal cells, suggesting that CXCR4 may play a critical role in regulating the tumor microenvironment as observed for other genes that are highly expressed in CRC-associated stromal cells [60,61]. The expression patterns of CXCR4 in our study were consistent with prior reports that analyzed CXCR4 expression in CRC.…”
Section: Discussionsupporting
confidence: 91%
“…Molecular biological analyses have shown that higher density of stroma with CAFs and FAP overexpression within the tumour is associated with increased tumour migration, invasion and therapy resistance [7,28,29]. Furthermore, higher FAP expression is seen in invasive areas of tumours such as tumour borders and microscopic tumour cell protrusions, also known as invadopodia [30,31]. These elements and areas of higher malignancy are linked with increased therapy resistance, likelihood of tumour recurrence and consequently worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, CAFs have been shown to be highly heterogeneous and better markers are currently needed to identify subtypes and shed light on their potential prognostic/predictive value in CRC [104]. The combination of stroma quantification with a functional activity assessment of CAFs might lead to an improved stroma-based tool for patient stratification [105].…”
Section: Stromal Densitymentioning
confidence: 99%